Pengaruh Kualitas Pelayanan, Citra Perusahaan dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Pada Perusahaan Daerah Air Minum di Kota Probolinggo - Tumini; M. Saiful Bahri; Irvan Sumiafandi (RELASI : JURNAL EKONOMI, 2020)
This study aims to determine the effect of service quality, company image and customer satisfaction on customer loyalty in the local water company (PDAM) in Probolinggo. This study uses a quantitative approach with descriptive approaches and associative analysis. The method of data collection is by distributing questionnaires (questionnaires), observation, documentation and literature study. The data sources used are primary data in the form of a general description of the company and the results of distributing questionnaires and secondary data in the form of explanatory quotes of variables obtained from books on related variables. The sampling technique used is nonprobability sampling with the current number of customers as many as 20,000. The method of data analysis is multiple linear regression analysis using the help of SPSS 23 for Windows. The results showed that (1) simultaneously (together) service quality, company image and customer satisfaction had a significant effect on customer loyalty in the municipal water company (PDAM) of probolinggo, (2) partially (separately) service quality, image company and customer satisfaction have a significant effect on customer loyalty in the municipal water company (PDAM) of probolinggo, (3) the most dominant customer satisfaction variable affects the variable customer loyalty in the local water company (PDAM) in Probolinggo.